DETERMINANTS OF FACTORS AFFECTING ISLAMIC SOCIAL REPORTING DISCLOSURES - Juwita, Rahma Dwi; Fitranita, Vika (I-Finance Journal, 2023)
This study aims to determine the effect of Company Size, Company Age, Sales Growth, and Sharia Compliance on Disclosure of Islamic Social Reporting (ISR) (Case Study on Islamic Commercial Banks in Indonesia 2018-2021). The population in this study is Islamic Commercial Banks in Indonesia which have sufficient annual reports for 4 years in the 2018-2021 period. The sample of this study used purposive sampling method and banks that met the criteria were 11 Islamic Commercial Banks so that the total number was 44 samples. The analysis technique used is multiple linear regression analysis with the F test hypothesis test and t test using IBM SPSS 26 as data processing software. The results showed that company size has a positive and significant effect on Islamic Social Reporting (ISR) disclosure. Based on the test results of 4 hypotheses, it can be concluded that company size has a positive effect on the disclosure of Islamic Social Reporting. While company age, sales growth, and sharia compliance have no positive effect on the disclosure of Islamic Social Reporting.